(untitled) (Annals of Bangladesh Agriculture, 2020)
The present study was conducted to determine the effects of organic carbon on soil structural stability and establish a correlation between soil aggregates with carbon (C) sequestration and different ratios of basic cations. Five treatments viz. control, cowdung, vermicompost, rice straw and poultry manure were laid out in a randomized complete block design in Boro rice cultivation where organic materials were applied considering 2 t C ha-1 except the control. The data revealed that different organic amendments insignificantly influenced soil carbon sequestration and water stable soil aggregates. However, a positive effect was found on C enhancement of soil with vermicompost and poultry manure treatments. Nonetheless, a positive relationship between total stable soil aggregates and C sequestration at crop harvest was also noticed. Improvement in soil aggregates followed the order of rice straw>poultry manure>vermicompost>cowdung treatments. Monovalent cationic ratios and cationic ratios on structural stability of soil significantly increased the stable soil aggregates of 0.25 mm sized particles at crop harvest. Ann. Bangladesh Agric. (2019) 23(1) : 15-24